2020
DOI: 10.1021/acs.jpcc.0c08870
|View full text |Cite
|
Sign up to set email alerts
|

DFT Accurate Interatomic Potential for Molten NaCl from Machine Learning

Abstract: Molten alkali chloride salts are a critical component in concentrated solar power and nuclear applications. Despite their ubiquity, the extreme chemical reactivity of molten alkali chlorides at high temperatures has presented a significant challenge in characterizing atomic structures and dynamic properties experimentally. Here, we investigate molten NaCl by performing high-temperature molecular dynamics simulations using a Gaussian approximation potential (GAP) trained on density functional theory (DFT) data … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 69 publications
(169 reference statements)
4
43
2
Order By: Relevance
“…Along the same line, Tovey et al . had used SOAP descriptors with GPR to generate a Gaussian approximation potential for molten NaCl with a RMSE of energy as 1.5 meV/atom [133] . They showed that the computed self‐diffusion coefficients of Na + and Cl – ions from MD simulations using this potential agree well with experimental results.…”
Section: Selected Examplesmentioning
confidence: 89%
“…Along the same line, Tovey et al . had used SOAP descriptors with GPR to generate a Gaussian approximation potential for molten NaCl with a RMSE of energy as 1.5 meV/atom [133] . They showed that the computed self‐diffusion coefficients of Na + and Cl – ions from MD simulations using this potential agree well with experimental results.…”
Section: Selected Examplesmentioning
confidence: 89%
“…where V is the volume, j(t) = Σ N i=1 q i • v i (t) is the current with the q i being the ionic charge and v i (t) velocity at time t. The benchmark of the code implementation is discussed elsewhere. 21…”
Section: Ionic Conductivitymentioning
confidence: 99%
“…18,20 Recently, we showed that many-body polarization in NaCl melts can be captured accurately by using MLP simulations scaled to ∼10,000 atoms with near Density Functional Theory (DFT) accuracy. 21 At these spatiotemporal scales, structural heterogeneity and ensemble averaging can be incorporated meaningfully into calculations, combining the accuracy of DFT with the statistical sampling of classical interatomic potentials. Despite these successes, the application of MLPs to the broader chemical space of molten salts is challenged by the difficulty of MLP parametrization.…”
mentioning
confidence: 99%
“…38 Consequently, short-ranged ML potentials are now commonly applied to study polar and even ionic systems. 34,[39][40][41] However, the importance of long-range effects will clearly depend on the material and property of interest and thus demands more systematic scrutiny. 42 For example, ionic diffusion in electrolytes may lead to the transient local accumulation and depletion of charges, which can break the isotropy of the electrostatic environment.…”
Section: Introductionmentioning
confidence: 99%